Extractives for development: Ten main messages - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Countries face both challenges and opportunities in using their extractive industries to achieve more inclusive development - particularly in the developing world. Yet while a large national income can result from resource wealth, it can also be associated with acute social inequality and deep poverty. Many countries struggle to diversify their economies, and create redistributive fiscal systems. The very worst cases see violent conflict and civil war. The expression "resource curse" has in turn become common coin. This paper presents 10 main messages from a UNU-WIDER Project, that should underpin efforts to improve development and environmental outcomes in the extractive industries.
Keywords: O20; O44; Q02; Q32; Q33; Q40; 330; extractive industries; resource wealth; resource curse; inequality; poverty; fiscal systems